HUBUNGAN PENGETAHUAN CARA MENERAN DENGAN KELANCARAN PERSALINAN KALA DUA PADA IBU BERSALIN PRIMIGRAVIDA PADA KEJADIAN ASFIKSIA BAYI BARU LAHIR DI PUSKESMAS KADUR KABUPATEN PAMEKASAN - Sri Tatik Andayani; Kinanatul Qomariyah (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2021)
Childbirth is a process in which the fetus and the amniotic fluid is pushed out through the birth canal. On his second stage becomes stronger and faster, about 2 to 3 minutes. Based on the results of research in health centers Kadur Pamekasan 2012, almost entirely (93.55%) of the second stage of labor on maternal primigravida smoothly. The purpose of this study is a known relationship to the smooth meneran knowledge of how the second stage of labor on maternal primigravida. This was a correlational analytical approach to Cross Sectional. Its population is a maternal primigravida in a health center of Kadur 2012, amounting to 31 people. Sampling technique using saturation sampling as many as 31 respondents. The collection of primary data obtained by giving questionnaires to the respondents and secondary data from the partograf check list at Kadur health center. Statistical tests using Spearman's Rank with SPSS version 17.0 with a significant level of 0.05. From the result showed that out of 11 respondents who have sufficient knowledge, nearly all (81.8%) as many as 9 mother of two current stage of labor and a small proportion (18.2%) which is about two mothers of two non-current stage of labor. While the four respondents who had a poor knowledge of the whole (100%) two current stage of labor. The results of statistical tests with Spearman's P = 0.510 rhank show, and p> a significant level (0.05) H0 accepted then it means there is no relationship between knowledge of how to give birth and the smoothness of second stage of labor on maternal primigravida in the incidence of neonatal asphyxia.